Análisis vertical del estado de resultados de la empresa Ecua&Wood Cew Export de la ciudad de Guayaquil, del periodo 2021-2022. - Cagua Boza, María Del Carmen (2024)
Analysis of the income statement allows us to see how the company is doing in terms of profits and losses. By reviewing it periodically, we can identify areas of opportunity to improve revenue or reduce expenses. In this way, the manager has a valuable tool to make decisions that positively impact financial results. If we review the income statement by period we can notice trends such as: income categories that are growing, others that are stagnant, costs that are getting out of control. Thus, based on real data, strategies can be implemented to take advantage of the company's strengths and address its weaknesses. The vertical analysis of the income statement will make it easier for us to evaluate the behavior of the accounts over time and compare them with industry standards. By analyzing vertically, we can see how much of the total income is allocated to each item such as sales costs, operating expenses, financial expenses. In this way, we can identify areas of opportunity to improve profitability.